Literature Review: Accounting For Assets and Liabilities In Local Government Financial Statements - niken, Niken Yulistika; Tuti Dharmawati (Journal of Scientific Interdisciplinary, 2024)
This study's objective is to help us comprehend how assets and liabilities are categorized and journalized in local government financial reports. Using a qualitative methodology, this study gathers data by reviewing existing literature. Data is collected by tracing and examining information or results from multiple sources, including books, proposals, articles, and relevant journals. The information gathered was then analyzed and arranged systematically, both from internal and external sources. Systematically, both from internal and external sources, and then described in the form of a narrative. In a narrative format. Based on the results of the literature study review, it can be concluded that all the sources analyzed agreed that assets and liabilities assets and liabilities must be clearly classified based on certain categories, such as current assets, fixed assets, current liabilities, and non-current liabilities followed by appropriate accounting journaling, and with appropriate accounting journaling, which reflects the transactions that have occurred and ensures that the declaration of finances occur and ensure that the declaration of finances reflect the true financial condition financial condition.